Exploring the influence of polymers on soil ecosystems: prospective from agricultural contexts - Sethi, Debadatta; Mohanty, Shraddha; Mohapatra, Kiran Kumar; Dash, Prava Kiran; Sahoo, Sanjib Kumar; Padhan, Kshitipati; Kusumavathi, Konathala; Majhi, Rajanikanta; Panda, Narayan; Pattanayak, Sushanata Kumar (Frontiers in Chemical Engineering, 2024)
The utilization of advanced polymeric materials has indeed emerged as a significant trend in sustainable agriculture, offering a range of innovative applications aimed at enhancing productivity, minimizing environmental impact, and promoting resource efficiency. Smart polymeric materials enable the controlled release of pesticides, herbicides, and fertilizers, thereby enhancing their efficacy while reducing the quantities needed. Superabsorbent polymeric materials act as soil conditioners, assisting in alleviating the negative impacts of drought by retaining moisture and enhancing soil structure. This fosters improved plant growth and resilience in water-scarce environments. Polycationic polymers play a role in plant bioengineering, facilitating genetic transformation processes aimed at enhancing crop productivity and disease resistance. Advanced polymeric systems contribute to the arsenal of precision agriculture tools by enabling precise delivery and targeted application of agricultural inputs. This approach enhances resource efficiency, reduces waste, and minimizes environmental impact while optimizing crop yields. In reviewing recent developments in the design and application of advanced polymeric systems for precision agriculture, several key considerations emerge.